Food and nutrition surveillance of Brazilian adolescents: possibilities with PeNSE data (Research, Society and Development, 2021)
The intensification of the Food and Nutritional Surveillance (FNS) of adolescents is essential for improving the management and production of care for this age group in Brazil. Thus, the objective of this study was to describe processes for the treatment of variables from the microdata bank of the National Adolescent Health Survey (PeNSE) and to present multivariate methods that can be used in the production of information for FNS of adolescents in Brazil from this populational survey. This is a methodological study based on sample 2 of PeNSE 2015. The main contributions are the description of aspects of PeNSE; considerations about the ethics of research with secondary data; guidance on microdata banks and preparation for analysis; the treatment of variables of interest to FNS - nutritional status, food consumption (estimate of sustainability standards and indicators); composite variables related to the eating behavior of adolescents; and the multiple analysis techniques with categorical data that can be used in association studies. It is noteworthy that the actions of food and nutrition surveillance of adolescents in Brazil can be qualified from the intensification of adequate epidemiological studies with data from PeNSE.